(untitled) (Journal of Medical & Health Sciences Review, 2025)
In the treatment of liver tumors, minimally invasive surgery (MIS) is used widely these days. The robotic technology is used in MIS these days. This study examines the current position robotic donor hepatectomy and MIS in literature and assess any future potential ramifications during transplant sector which is usually done by robots. Nevertheless, although living donors have emerged to supplement deceased donors as a source of organs, supply has fallen well short of need. Therefore, in recent decades, rationing has been a negative focus. The fundamental idea of organ shortage may soon be in jeopardy due to recent changes in the epidemiology of liver illness and groundbreaking advancements in liver preservation. The emphasis will shift to enhancing fair access while removing barriers related to infrastructure, workforce development for organ recovery and rehabilitation, and related expenses. Liver preservation research is enhancing transplantation conditions. Several benefits of robotic surgery have been cited, such as three-dimensional (3-D) imaging that produces a constant, high-definition image, the absence of hand tremors, mobility; compare to laproscopic surgery the shorter learning curve and the lack of hand tremors.